PERSEPSI REMAJA TERHADAP SEKS PRANIKAH DI DESA PULAU RUMPUT KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - ", Masela; Kadarisman, Yoskar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Earch was conducted on teenagers in Pulau Rumput Village, Gunung Toar District, Kuantan Singingi Regency. The purpose of this study was to find out how the perceptions of teenagers in Pulau Rumput Village on premarital sexual behaviour in Pulau Rumput Village. The population was 68 teenagers from Pulau Rumput. The population was chosen by using Slovin formula so that the sample of 68 people was obtained. To analyzed the data, SPSS version 23 was utilized. Based on the results of data analysis, it is known that the perceptions of teenagers in Pulau Rumput Village are negative for premarital sex, which means that they already know and understand that premarital sex is deviant behaviour. The suggestions given by the author based on the results of the data analysis carried out are as follows: teenagers are suggested to be able to further improve their knowledge about things related to premarital sex, learning and obedience to religion, find friends who support more positive activities in order to avoid sexual behaviour premarital. Besides, they also suggested to not do prohibited things while dating.The higher incidence of pregnancy outside marriage, the better teenagers maintain themselves in the association. To parents, it is suggested to provide more guidance and good supervision for their children, so that teens do not fall into bad relationships.Keywords: Perception And Premarital Sexual